Kepemimpinan Yang Melayani (Servant Leadership) : Sebuah Kajian Literatur - Dimas Ardi Nugraha; Ananta Fani Aprilia; Robiatul Awaliyah; Mochammad Isa Anshori (Jurnal of Management and Social Sciences, 2023)
This study aims to explain the concept of servant leadership and describe how this approach can build a sustainable and positive impact organization. The research method used is literature study by reviewing academic articles, journals, books, and other relevant sources. The results of the analysis show that servant leadership emphasizes the importance of creating a wider positive impact on society and the environment. Servant leaders consider the social, economic, and environmental implications of their decisions and actions. Servant leadership can help organizations respond with flexibility to changes that occur in a dynamic business environment. Keywords: servant leadership, organization, environment, community